Hallucination‐ and speech‐specific hypercoupling in frontotemporal auditory and language networks in schizophrenia using combined task‐based fMRI data: An fBIRN study. Issue 4 (21st December 2017) - Lavigne, Katie M.; Woodward, Todd S.
Abstract: Hypercoupling of activity in speech‐perception‐specific brain networks has been proposed to play a role in the generation of auditory‐verbal hallucinations (AVHs) in schizophrenia; however, it is unclear whether this hypercoupling extends to nonverbal auditory perception. We investigated this by comparing schizophrenia patients with and without AVHs, and healthy controls, on task‐based functional magnetic resonance imaging (fMRI) data combining verbal speech perception (SP), inner verbal thought generation (VTG), and nonverbal auditory oddball detection (AO). Data from two previously published fMRI studies were simultaneously analyzed using group constrained principal component analysis for fMRI (group fMRI‐CPCA), which allowed for comparison of task‐related functional brain networks across groups and tasks while holding the brain networks under study constant, leading to determination of the degree to which networks are common to verbal and nonverbal perception conditions, and which show coordinated hyperactivity in hallucinations. Three functional brain networks emerged: (a) auditory‐motor, (b) language processing, and (c) default‐mode (DMN) networks. Combining the AO and sentence tasks allowed the auditory‐motor and language networks to separately emerge, whereas they were aggregated when individual tasks were analyzed. AVH patients showed greater coordinated activity (deactivity for DMN regions) than non‐AVH patients during SP in all networks, but this did not extend to VTG or AO. This suggests that the hypercoupling in AVH patients in speech‐perception‐related brain networks is specific to perceived speech, and does not extend to perceived nonspeech or inner verbal thought generation.